Disclosure of Corporate Information to Trade Unions in North America - Jain, Hem (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
The focus of this paper is on the information disclosed by companies in the private sector to trade unions in North America, with particular reference to Canada.